Pengaruh Top of Mind Terhadap Keputusan Pembelian Convenience Goods di Supermarket Mo-Ro Mall Purwokerto - Wahyu Eko Prasetyanto (JBIMA (Jurnal Bisnis dan Manajemen), 2015)
Purchasing decisions by consumers is very important, because it is one measure of the success of marketing strategies and tactics that have been made by a company. Consumers tend to buy brands that are well known because they feel safe to something already known. Consumers who have the highly brand awareness, predicted to be more loyal. Each manufacturer will try to brand its products can occupy the position of top of mind in the minds of consumers, as it will facilitate and accelerate decision-making or purchasing a product. The importance of that brand their products become top of mind in the minds of the purchase decider increasingly felt for convenience goods product manufacturer; namely consumption goods are often necessary (and purchased) on a regular basis, instantly / immediately and requires only a minimum of effort to get it. This study attempts to examine further how much top of mind can really influence purchase decisions on products of convenience goods. The research was conducted on visitors Supermarket Mo-Ro Purwokerto.